Assessment on disposal practices of unused and expired medications - Athira Sunil; Amritha Alice; Venkateswaramurthy Nallasamy; Sambathkumar Ramanathan (Intelektual Pustaka Media Utama, 2022)
Pharmaceutical disposal practices have become a global issue that has caught the concern of health authorities, pharmaceutical firms, healthcare practitioners, and the general public. The current study aimed to assess the disposal practices of unused and expired medications among the households Namakkal district, Tamil Nadu, India. The qualitative, cross-sectional study was conducted using a well-structured questionnaire form. A total of 400 responses were obtained from each member of the family. Participants under the age of 18 were excluded from the study. Respondents who refused to participate were not included in the study. More than 50% of the study population reported that they stored unused and expired medications at home. Most of the participants revealed that the unused medications they stored costs approximately ≤₹300. Majority of participants dispose unused/expired medications by means of trash can (53.1%). A significant population (71.2%) was unaware of novel disposal practices like drug take-back system. The study concluded that there is an inappropriate disposal practice among households which has to be rectified by providing awareness among the public. Further studies should be conducted for the development of well formalized protocol regarding proper disposal practices.